Analisis Laporan Keuangan Perusahaan-Perusahaan Go Public Sektor Pertambangan Yang Terdaftar di BEI - Seli Nurdianti; Zulkarnain Zulkarnain (Institut Manajemen Wiyata Indonesia, 2020)
This report analyzes the financial position (Balance Sheet) and the income statement of the mining sector, comparing reports that ended as of December 31, 2018 and 2017. Data in this report represent four mining sizes and three types of mining sub-sectors. This study aims to provide an overview and find out the financial performance of mining sector companies with measuring tools or indicators used in measuring the financial performance of the mining sector is the annual financial statement financial ratios. Quantitative approaches are used in data analysis and then the results of data analysis are done descriptively with secondary data obtained from financial statements to illustrate the findings of the analysis results related to the data. The results of the discussion found that the financial performance of companies grouped by size and type in the mining sector 2017 and 2018 seemed to be with a fluctuating ratio, this was due to an increase or decrease in financial statement items, for example in cash, debt, sales, inventory, profits , and others.